Absence of Irreversible Effects of Aliskiren in Standard Juvenile Rat Toxicity Studies. (1st April 2014) - Beckman, David; Barbeau, Stephanie; McLean, Lee Anne; Yan, Jing‐He; Hoffmann, Peter
<x xml:space="preserve">Abstract</x> BACKGROUND Aliskiren is the first orally bioavailable direct renin inhibitor approved for the treatment of hypertension in adults. Juvenile toxicity studies in rats were initiated to support treatment in the pediatric population. METHODS In Study 1, aliskiren oral administration was initiated on postpartum day (PPD) 14, after nephrogenesis was completed, and continued through PPD 70 at doses of 0, 30, 100, and 300 mg/kg/day. In‐life, clinical pathology, anatomic pathology, developmental, behavioral, reproductive, and toxicokinetics evaluations were performed. In Study 2, oral administration was initiated on PPD 8, before completion of nephrogenesis, and continued through PPD 35/36. In‐life, clinical pathology, anatomic pathology, developmental, and toxicokinetics evaluations were performed. RESULTS With dosing initiated on PPD 8, mortality at 100 and 300 mg/kg/day and slightly increased kidney weight at 100 mg/kg/day occurred. Decreased absolute lymphocyte count at 300 mg/kg/day at the end of dosing occurred with dosing initiated on PPD 14. There were clinical signs and transient effects on body weight gains in both studies. There were no changes in other parameters. Systemic exposure was much higher on PPD 8 and 14 compared with adult rats on PPD 64. CONCLUSIONS All effects produced by aliskiren, including kidney effects, were reversible. Increased exposure in very young animals is considered to be the result of immature drug transporter systems.